Penggunaan Metode Autoregressive Integrated Moving Average untuk Meramalkan Nilai Tukar Petani di Sumatera Barat - Yosela, Fiera; Arnellis, Arnellis (Journal of Mathematics UNP, 2022)
Resident of West Sumatra is mostly absorbed in the agricultural sector. The welfare of farmers is the main priority which is believed to be in development in that sector. Therefore we need a benchmark to measure prosperity of peasant, either is farmer’s exchange rate. This study has goal of get best ARIMA model to predict the farmer’s exchange rate of West Sumatra. Research results to get greates model ARIMA (1,1,1) have smallest MSE vaIue 2681^(-9). The shape of the model is Y_t^0.09=0.0005685-0.5270Y_(t-1)^0.09+Y_(t-1)^0.09+0.5270Y_(t-2)^0.09+0.9921e_(t-1)+e_t.